Preliminary evaluation of knee kinetics in female athletes on hormonal contraceptives - Gilmer, G.; Oliver, G. D. (International Journal of Sports Medicine, 2020)
Recently, an emphasis has been placed on understanding how ovarian sex hormones and hormonal contraceptives affect risk for anterior cruciate ligament (ACL) injury. The literature presents large discrepancies in whether or not hormonal contraceptives affect ACL injury risk; therefore, the purpose of this study was to evaluate whether vertical ground reaction force (GRF) and knee valgus force are different between athletes who do and do not use hormonal contraceptives. Twenty-two female athletes volunteered to participate and were divided into two groups based on their answers to a health history questionnaire: those who use hormonal contraceptives and those who do not. Participants performed a drop vertical jump (DVJ) and single leg crossover dropdown (SCD) at two different time points in their menstrual cycle (pre-ovulatory phase and mid-luteal phase). Kinetic data were collected at 1000 Hz. Independent samples t-tests revealed no significant differences between groups in vertical GRF and knee valgus force at both time points. Findings from this study suggest that hormonal contraceptives do not elicit detectable changes in vertical GRF and knee valgus force. Ultimately, this calls for further studies on the relationship between hormones and ACL injury risk and physicians to consider hormonal screening in addition to neuromuscular and biomechanical screening. Key words anterior cruciate ligament - hormonal screening - injury prevention